Preliminary proteomic characterisation of primodia and vegetative dikaryotic mycelial cells from tiger’s milk mushroom (Lignosus rhinocerus) - Wei, Hong Lai; Teik, Kee Leo; Zamri Zainal,; Fauzi Daud, (Universiti Kebangsaan Malaysia, 2014)
Tiger’s Milk mushrooms (Lignosus rhinocerus) are polypores with three distinct parts: cap (pileus), stem (stipe) and tuber (sclerotium). The stem of this medicinal mushroom is centrally connected to the brownish woody cap that grows out from the tuber underground rather than from the wood. To date, the biotic and abiotic factors that induce the growth of this mushroom are unclear and information regarding its development is scanty. Hence, the differential protein expressions of vegetative dikaryotic mycelial and primordial cells of this mushroom were investigated. Six two dimensional-sodium dodecyl sulfate-polyacrylamide gel electrophoresis (2D-SDS-PAGE) of 13 cm with pH3-10 containing the intracellular proteins of vegetative mycelial and primordial cells of L. rhinocerus were obtained. Analysis of 2D-SDS-PAGE using Progenesis Samespot version 4.1 yielded approximately 1000 distinct protein spots in the proteome of vegetative mycelial cells, while primordial proteome contained nearly 100 spots. Further comparison between the vegetative mycelial and primordial proteomes yielded significant up-regulation of protein expression of 5 primordial cells proteins that were labeled as P1, P2, P3, P4 and P5. These protein spots were excised, trypsin digested and submitted to mass spectrometry. Protein identification through MASCOT yielded significant identification with P1 and P2 as DnaJ domain protein, P3 and P5 as hypothetical protein while P4 as AP-2rep transcription factor. The present results suggested that P3, P4 and P5 are novel proteins that involved in the initiation of L. rhinocerus primordia. Our findings also suggested that stress response mechanism is present during fruitification of this mushroom.